Nontuberculous mycobacteria in respiratory samples from patients with pulmonary tuberculosis in the state of Rondônia, Brazil - de Lima, Cleoni Alves Mendes; Gomes, Harrison Magdinier; Oelemann, Maraníbia Aparecida Cardoso; Ramos, Jesus Pais; Caldas, Paulo Cezar; Campos, Carlos Eduardo Dias; Pereira, Márcia Aparecida da Silva; Montes, Fátima Fandinho Onofre; de Oliveira, Maria do Socorro Calixto; Suffys, Philip Noel; Moura, Maria Manuela da Fonseca (Memórias do Instituto Oswaldo Cruz, 2013)
The main cause of pulmonary tuberculosis (TB) is infection with Mycobacterium tuberculosis (MTB). We aimed to evaluate the contribution of nontuberculous mycobacteria (NTM) to pulmonary disease in patients from the state of Rondônia using respiratory samples and epidemiological data from TB cases. Mycobacterium isolates were identified using a combination of conventional tests, polymerase chain reaction-based restriction enzyme analysis of hsp65 gene and hsp65 gene sequencing. Among the 1,812 cases suspected of having pulmonary TB, 444 yielded bacterial cultures, including 369 cases positive for MTB and 75 cases positive for NTM. Within the latter group, 14 species were identified as Mycobacterium abscessus , Mycobacterium avium , Mycobacterium fortuitum , Mycobacterium intracellulare , Mycobacterium gilvum , Mycobacterium gordonae , Mycobacterium asiaticum , Mycobacterium tusciae , Mycobacterium porcinum , Mycobacterium novocastrense , Mycobacterium simiae , Mycobacterium szulgai , Mycobacterium phlei and Mycobacterium holsaticum and 13 isolates could not be identified at the species level. The majority of NTM cases were observed in Porto Velho and the relative frequency of NTM compared with MTB was highest in Ji-Paraná. In approximately half of the TB subjects with NTM, a second sample containing NTM was obtained, confirming this as the disease-causing agent. The most frequently observed NTM species were M. abscessus and M. avium and because the former species is resistant to many antibiotics and displays unsatisfactory cure rates, the implementation of rapid identification of mycobacterium species is of considerable importance.